In vitro toxicity of new engineered nanoparticles through their life cycle - Irfan, Muhammad Adeel (Cranfield University, 2013)
The rapid development of nanotechnology has caused concerns about nanoproducts on human health throughout their lifecycle. As part of the consortium NEPHH (nanomaterial related environmental pollution on human health through their life cycle, funded by EU-FP7), this project aimed to assess the potential effect of novel polymer-silicon composites on human health from a lifecycle perspective, focusing on in vitro toxicity of raw silica nanoparticles (SiNP) and dust nanoparticles (NP) released from silicon-based polymer composites. The main objectives were to characterise a group of amorphous SiNP and dust NP in water and cell culture medium; assess NP toxicity potential in in vitro models; and establish mode of SiNP action. The selection of SiNP of size 7-14 nm was based on their wide use in developing polymer nanocomposites. Dust NP were generated from mechanical processing of polymer composites made of polyamide-6 (PA6), polyurethane (PU) and polypropylene (PP), each incorporated with SiNP or 3 other different silicon reinforcement materials. The dispersion and size of NP in water and in cell culture medium were characterized using dynamic light scattering, scanning electron microscopy and transmission electron microscopy. The chemical composition of NP was assessed by infra-red spectroscopy. NP were assessed in vitro for induction of membrane damage, intracellular reactive oxygen species (ROS), loss of cell viability, and cellular uptake by flow cytometry and confocal microscopy. In order to identify potential biomarkers for toxicity prediction, miRNA array and extracellular metabonomic assays were performed. The size of SiNP (10-100 µg/ml) ranged from ~200-500 nm in water and ~20- 500 nm in culture medium, indicating the presence of aggregates. The infra-red spectrum of SiNP dried from culture medium showed a slight difference as compared with that dried from water, indicating protein adsorption. SiNP induced acute ROS increase, cell membrane damage, and reduction in cell viability after 48 h in human lung carcinoma epithelial A549 cells, lung fibroblast MRC-5 cells and skin HaCaT keratinocytes. SiNP were up taken by all 3 cell types, and located in the cytosol. Six early (<48h) SiNP responsive miRNAs were identified in A549 cells. SiNP also induced early changes in metabolites including glucose, lactate, ethanol, phenylalanine, histidine and tyrosine. Dust NP generated from PA6 group materials were more toxic than those from other polymer composites when assessed at 25-100 µg/ml at 72 h in A549 cells. The results obtained from this study suggest that 1) both small and larger SiNP aggregates are taken up into the target cells; 2) conventional cytotoxicity assays combined with miRNA and metabonomic assays provide insight into the molecular mechanisms of the nanotoxicity; 3) metabonomics and miRNA assays can serve as robust tools for recognising sub-toxic dose-effect relationships; 4) the toxicity of dust NP from polymer composites depends on polymer type but not reinforcement materials. This study demonstrated the importance of lifecycle analysis as opposed to single stage analysis of novel materials. Further studies need to improve study design to enable interpretation of cytotoxicity in relation to NP size, physiochemical property and intracellular dose, and to simulate the health effect of polymer-silicon composites under more realistic scenarios.
Keywords: Nanotoxicology; Silica; in vitro; physical characterisation; life cycle analysis